First detection of ozone in the mid-infrared at Mars: implications for methane detection - Olsen, KS; Lefèvre, F; Montmessin, F; Trokhimovskiy, A; Baggio, L; Fedorova​, A; Alday​, J; Lomakin​, A; Belyaev, DA; Patrakeev, A; Shakun​, A; Korablev, O (EDP Sciences, 2020)
Aims: The ExoMars Trace Gas Orbiter (TGO) was sent to Mars in March 2016 to search for trace gases diagnostic of active geological or biogenic processes.